2002
DOI: 10.1038/sj.bjc.6600618
|View full text |Cite
|
Sign up to set email alerts
|

15-PGJ2, but not thiazolidinediones, inhibits cell growth, induces apoptosis, and causes downregulation of Stat3 in human oral SCCa cells

Abstract: Activation of peroxisome proliferator-activated receptor gamma (PPARg) has been linked to induction of differentiation, cell growth inhibition and apoptosis in several types of human cancer. However, the possible effects of PPARg agonists on human oral squamous cell carcinoma have not yet been reported. In this study, treatment with 15-deoxy-D 12,14 -PGJ 2 (15-PGJ 2 ), a natural PPARg ligand, induced a significant reduction of oral squamous cell carcinoma cell growth, which was mainly attributed to upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 58 publications
3
36
0
1
Order By: Relevance
“…Similarly, we recently demonstrated that 15d-PGJ 2 inhibits cell growth and induces apoptosis in oral SCC utilising PPARg-independent mechanisms (Nikitakis et al, 2002). Moreover, we suggested that the effects of 15d-PGJ 2 on oral SCC cells may be related to its ability to downregulate Stat3 (Nikitakis et al, 2002). In the present study, we investigated the effect of 15d-PGJ 2 on tyrosine kinases that regulate growth and survival of oral SCC cells, including JAKs and EGFR.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, we recently demonstrated that 15d-PGJ 2 inhibits cell growth and induces apoptosis in oral SCC utilising PPARg-independent mechanisms (Nikitakis et al, 2002). Moreover, we suggested that the effects of 15d-PGJ 2 on oral SCC cells may be related to its ability to downregulate Stat3 (Nikitakis et al, 2002). In the present study, we investigated the effect of 15d-PGJ 2 on tyrosine kinases that regulate growth and survival of oral SCC cells, including JAKs and EGFR.…”
mentioning
confidence: 75%
“…These effects, frequently attributed to activation of peroxisome proliferator-activated receptor gamma (PPARg), have been recently proven to be at least partially mediated through PPARg-independent pathways (Clay et al, 2001(Clay et al, , 2002Straus and Glass, 2001;Hsiang and Straus, 2002;Liu et al, 2003). Similarly, we recently demonstrated that 15d-PGJ 2 inhibits cell growth and induces apoptosis in oral SCC utilising PPARg-independent mechanisms (Nikitakis et al, 2002). Moreover, we suggested that the effects of 15d-PGJ 2 on oral SCC cells may be related to its ability to downregulate Stat3 (Nikitakis et al, 2002).…”
mentioning
confidence: 86%
“…Curcumin, an anti-inflammatory and a chemopreventive agent, negatively regulates JAK/STAT1 signaling through activation of SHP-2 (61). Sulindac, a chemopreventive agent used to prevent polyp formation in familial adenomatous polyposis patients, inhibits constitutive STAT3 activation in human oral squamous cell carcinoma (62), suggesting that sulindac induces cell death and inhibits cell proliferation at least in part through the inhibition of constitutive activation of STAT3 (63)(64)(65)(66)(67). Agonists of PPAR␥, 15d-PGJ2, and the antidiabetic rosiglitazone have been shown to suppress JAK/STAT signal- ing through the induction of SOCS1 and SOCS3, which are suppressors of cytokine signaling (38).…”
Section: Discussionmentioning
confidence: 99%
“…Target mRNA values were normalized by using ␤-actin mRNA as an internal control. The relative quantitation of gene expression was performed by using the comparative ⌬⌬C t (threshold method) with ␤-actin as an internal control (20).…”
Section: Methodsmentioning
confidence: 99%